ANALISIS PENGARUH PENCAMPURAN SEMEN PADA TANAH GAMBUT KUTARAYA TERHADAP NILAI CBR - Siti Muslikah; M. Agung; Hermawati Hermawati; Yosieguspa Yosieguspa; Sri Yulianti (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Peat soil is a soil that physically and technically does not meet the requirements and conditions in construction work. This study aims to evaluate the improvement of soil carrying capacity using cement stabilization methods, focusing on the value of California Bearing Ratio (CBR) unsoaked. Tests are carried out in laboratories to analyze the physical and mechanical properties of the soil. This research is intended to address the significant subsidence problem that can occur in road construction built on peat soil. The results showed that the CBR value of native soil was 3.00%. After the addition of 4% cement, the CBR value increases to 3.25%. At the addition of 6% cement, the CBR value fell to 2.50%, while at the addition of 8% cement, the CBR value reached 4.17%. It can be concluded that the greatest increase in the value of CBR occurs in the addition of 8% of cement. Thus, soil stabilization methods using cement mixtures can increase the CBR value of peat soils.